Effect of corporate governance mechanism on the earnings management strategies: Empirical evidence from publicly listed industrial firms in the Philippines - Acuin, Cholly Q. (Animo Repository, 2021)
This study aimed to determine the effects of corporate governance mechanism on earnings management strategies of publicly-listed industrial firms in the Philippines. It deals with efficient perspective of managers who performed earnings management strategies using Discretionary Accruals (DA) and Real Activities Management (RAM) through Cash Flows from Operations (CFO), Production Costs (PROD) and Discretionary Expenses (DIS EXP) and to further utilized firms’ corporate governance mechanism to shield the earnings management strategies performed. Also, variables were controlled in this study, including selected firm characteristics (profit, debt, and size). The study has examined 137 publicly listed firms in the Philippines for a three-year period from 2017 to 2019. Discretionary accruals were evaluated through Modified Jones (1991) by Dechow (1995). While real activities management was measured by deviations from normal operations which was termed as abnormal operations by Rowchudhury (2006). The finding on board independence was not only new, but also relevant, because while there was a growing interest on the reporting of non-financial information, this took for granted the reliability of financial information under certain corporate governance mechanism of being independent director. Another finding was very important to the fraction of diversity literature on boards in certain industries and specifically for electrical, energy, and power industry (EEP), which was vitally affecting stakeholders, regulators, and emerging countries like the Philippines. The result has confirmed that the board composition in electrical, energy, and power industry was also affected the unlikelihood to manage its earnings management (Krishnan & Parson, 2008; Srinidhi et al., 2011). Results of this study call for further investigation to address a number of limitations. As such, may broaden the coverage of regulation like laws and anti-trust to regulate certain provision. Furthermore, future researcher such as management of publicly listed firms, investors, academe and private sectors may benefit to a more indicator variables for corporate governance mechanism to better mitigate earnings management strategies and include the non-public firms in the Philippines and conduct industry analyses.